Asian Financial Statement Analysis : Detecting Financial Irregularities - Tan, ChinHwee; Robinson, Thomas R. (Wiley finance series., 2014)
Gain a deeper understanding of Asian financial reporting and how to detect irregularities The Asian region, and particularly China, is becoming a hotbed of investment activity. There have been quite a few accounting scandals in Asia in the recent years - now rivaling those we have seen in the Americas and Europe. Assessing potential or active overseas investments requires reliance on financial statements, the full parameters of which may vary from region to region. To effectively analyze statements, it is necessary to first understand the framework underlying these financial ...